PERSEPSI (TIDAK) ETIS MAHASISWA: PENGARUH LOVE OF MONEY DAN MACHIAVELLIAN - Elsya Panduwinasari; Nurafni Eltivia; Kurnia Ekasari; Hesti Wahyuni (STIE Mahardhika, 2020)
The purpose of this study is to examine the influence of the love of money and Machiavellian on the unethical perceptions of accounting students both partially and simultaneously. Respondents in this study were active students majoring in accounting at State Polytechnic of Malang. The sampling technique used purposive sampling with a sample size of 321 respondents. The data collection method uses a questionnaire containing 58 questions related to the love of money, Machiavellian, and unethical perception. The results of the study prove that the love of money has a significant and positive effect on the unethical behavior of accounting students. Machiavellian has a significant and positive effect on the unethical behavior of accounting students. Simultaneously the love of money and Machiavellian have a significant and positive effect on the unethical behavior of accounting students.